2005
DOI: 10.1152/physiolgenomics.00057.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal antibiotic treatment alters gastrointestinal tract developmental gene expression and intestinal barrier transcriptome

Abstract: The postnatal maturation of the gut, partially modulated by bacterial colonization, ends up in the establishment of an efficient barrier to luminal antigens and bacteria. The use of broad-spectrum antibiotics in pediatric practices alters the gut bacterial colonization and, consequently, may impair the maturation of the gut barrier function. To test this hypothesis, suckling Sprague-Dawley rats received a daily intragastric gavage of antibiotic (Clamoxyl; an amoxicillin-based commercial preparation) or saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 60 publications
8
96
1
4
Order By: Relevance
“…As described previously (35), when amoxicillin was administered to rats from PND7, drastic reductions in the amounts of the three bacterial genera were observed in the colon at PND15 (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
“…As described previously (35), when amoxicillin was administered to rats from PND7, drastic reductions in the amounts of the three bacterial genera were observed in the colon at PND15 (Fig. 1A).…”
Section: Resultssupporting
confidence: 80%
“…Although previous reports have indicated a transcriptional effect of b-lactam antibiotics (Rothstein et al, 2005;Schumann et al, 2005;Lee et al, 2008), it is unlikely that this represents an explanation for the observed enhancement of torsinA activity in all of our studies. First, the nematode screens that identified the enhanced activity were conducted with human torsinA variants that were ectopically expressed from distinct promoters in two different cell types: body wall muscles and DA neurons (Fig.…”
Section: Mechanistic Studiescontrasting
confidence: 62%
“…Culture-based microbial analysis of caecal contents Total aerobic and anaerobic bacteria were enumerated in selective media and incubation conditions according to Schumann et al [8]. Briefly, caecal samples were diluted in Ringer medium, and total aerobic and anaerobic bacteria were investigated by plating onto trypcase soy agar + 5% sheep blood (TSS) medium (Biomerieux, Lyon, France) for 24-48 h at 37°C under aerobic and anaerobic conditions.…”
Section: Methodsmentioning
confidence: 99%